Fast track surgery for knee replacement surgery: a lean six sigma approach. Issue 3 (6th January 2020) - Ricciardi, Carlo; Balato, Giovanni; Romano, Maria; Santalucia, Ida; Cesarelli, Mario; Improta, Giovanni
Abstract : Purpose: The reduction of costs has a more and more relevant role in the healthcare context, therefore, a large effort is done by health providers to this aim, for example, by reducing the length of hospital stay (LOS) of patients undergoing surgery. Fast track surgery fits perfectly this issue and was applied to patients undergoing knee replacement surgery due to Osteoarthritis, one of the most common diseases of aged population. The paper aims to discuss these issues. Design/methodology/approach: Lean six sigma was applied to analyze the implementation of fast track surgery through the define, measure, analyze, improve, control roadmap, used as a typical problem-solving approach. It is characterized by five operational phases, which make possible the achievement of fixed goals through a rigorous process of defining, measuring, analyzing, improving and controlling business problems. Findings: The corrective action, consisting in the application of fast track surgery, improved both effectiveness and efficiency of the process of care. The average length of hospital stay (LOS) was reduced from 8.34 to 6.68 days (–19.9 percent) and its standard deviation from 2.41 to 1.99 days (–17.1 percent). The statistical significance of this decrease was verified by means of proper tests. Moreover, some variables influencing the LOS were identified. Research limitations/implications: The follow up and the satisfaction of patients were not analyzed and could be a future development of this study. Practical implications: Patients will experience a faster recovery while the hospital will benefit from a rise of available beds. The effect is a general improvement of hospital management. Originality/value: The introduction of fast track surgery for patients undergoing knee replacement surgery made significantly reduce LOS and, consequently, costs' with a money saving of more than 50, 000 euro per year.